Peutz-Jeghers Syndrome: A Rare Case Report - Mohammad Shamsul Arfin; Khan Md Nazmus Saqeb; Mohammad Baharul Alam; Rebeka Razzaque (Bangladesh Critical Care Journal, 2025)
Peutz-Jeghers syndrome (PJS) is a hereditary polyposis syndrome of the gastro intestinal tract with multiple hamartomatous polyps affecting almost any part of the gastrointestinal tract with pigmentation around lips and buccal mucosa. It is inherited in an autosomal dominant pattern. Most patients present with complications induced by the polyps like ulceration, anemia, bowel intussusception and sometimes malignant transformation of the polyps. Moreover, these patients have an increased risk of malignancy in other non-gastrointestinal sites as well. Here we present a case of a 29 years old male who presented with recurrent bouts of melaena. The patient had perioral pigmentations. Endoscopy upper GI and colonoscopy revealed multiple polyps all over the GIT. Histologically they were confirmed to be hamartomas, suggesting a diagnosis of PJS. Aggressive screening is recommended in patients with Peutz-Jeghers syndrome to prevent malignancy. Upper GI endoscopy and colonoscopy along with ileoscopy should be performed every two years from 10 years of age. Surveillance for cancers outside GIT including testicular and breast examinations once in a year should be introduced in the second decade of life. Bangladesh Crit Care J March 2025; 13 (1): 56-59